Evaluation of Spirulina spp. Crude Extract Revealed Antimicrobial, Antioxidant and UV Photoprotective Properties - Calabrese, Megan Novela; Tianco, Catherine Anne Domingo; Garate, Adrian Michael Cinco; Tan, Maria Carmen Salandanan; Ting, Jasmine; Galian, Richard Anthony Ferrer; Bonto, Aldrin Porcioncula; Chang, Aimee Caye Garcia (Trends in Sciences, 2024)
The antimicrobial, UV photoprotective and antioxidant capabilities of Spirulina spp. methanolic extracts were determined using Fourier transform infrared spectroscopy (FTIR) and gas chromatography-mass spectrometry (GC-MS). Notable compounds were reported to be 5 fatty acid methyl esters, 4- methoxyallocinnamic acid, 2-ethylhexyl esters and bumetrizole. Moreover, these metabolites contained functionalities including hydroxyl, alkyl and carbonyl, as supported by the FTIR result. After 24 h, there was no zone of inhibition in the antibacterial activity as measured by the agar well diffusion method at doses of 30, 50 and 70 g/mL. The ABTS radical scavenging assay revealed that the methanolic Spirulina spp. exhibited an inhibitory concentration of 1,047.91 g/mL for antioxidant activity and SPF values of 0.40, 0.23 and 0.93 were calculated using Mansur’s equation for concentrations of 30, 50 and 70 g/mL, respectively. The results of the study showed the potential of cyanobacterial extracts as a bioactive ingredient in cosmetic product development. HIGHLIGHTS Methanolic extraction of Spirulina spp. comprises 5 fatty acid methyl esters, 4-ethoxyallocinnamic acid 2-ethylhexyl esters and bumetrizole characterized by GC-MS. Constituents of the extract contain functional groups including –OH, –C–H and C=O. The extracts were classified as weak radical stabilizers, confirmed by ABTS assay and possessed UV photoprotective capacity confirmed by the in vitro SPF assay. GRAPHICAL ABSTRACT